PENGARUH PERSEPSI KEGUNAAN, KEMUDAHAN TERHADAP NIAT MENGGUNAKAN SISTEM E-FILING, E-BILLING, E-REGISTRATION DENGAN KEPERCAYAAN SEBAGAI INTERVENING - Ade Budi Setiawan; Didi Didi; Hanifah Atika Sari (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2023)
This study aims to determine the effect of perceived usefulness and perceived ease of use on intentions to use e-filing, e-billing and e-registration systems and to determine the effect of perceived usefulness and perceived ease of use on intention to use through trust as an intervening variable at KPP Pratama Jakarta Jatinegara . The population in this study were individual taxpayers registered at KPP Pratama Jakarta Jatinegara with a total of 63 taxpayers as respondents. The sampling technique carried out by researchers is using the Accidental Sampling technique. Data analysis uses the help of Partial Least Square (PLS). The results of this study indicate that perceived usefulness, perceived ease of use and trust influence the intention to use. Trust cannot intervene in the effect of perceived usefulness on intention to use, whereas trust can intervene in the effect of perceived ease of use on intention to use.